2019
DOI: 10.15171/jcvtr.2019.35
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cigarette smoking on infarct location and in-hospital outcome following acute ST-elevation myocardial infarction

Abstract: Introduction: Smoking, which is a major modifiable risk factor for coronary artery diseases, affects cardiovascular system with different mechanisms. We designed this study to investigate the association of smoking with location of ST-segment elevation myocardial infarction (STEMI), and short-term outcomes during hospitalization. Methods: In 1017 consecutive patients with anterior/inferior STEMI, comprehensive demographic, biochemical data, as well as clinical complications and mortality rate, were recorded. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
3
3
1
1
Order By: Relevance
“…In our study, we showed that smokers less likely to have diabetes and hypertension which were statistically significant compared to non-smokers this was in agreement with Toluey M, et al (13) findings.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we showed that smokers less likely to have diabetes and hypertension which were statistically significant compared to non-smokers this was in agreement with Toluey M, et al (13) findings.…”
Section: Discussionsupporting
confidence: 93%
“…This difference in rates of inhospital outcome is possibly due to eligibility criteria of patients as in our study we included high-risk patients who did not receive reperfusion therapy while their studies have included all patients with acute myocardial infarction. [11][12][13][14][15][16]. While there are also some studies whose observations are contrary with our study findings such as hypertension and dyslipidemia were also associated with increased rates of inhospital mortality in their studies [17,18].…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we showed that smokers were less likely to have diabetes and hypertension which were statistically significant compared to non-smokers this was in agreement with Toluey M, et al [13] findings.…”
Section: Discussionsupporting
confidence: 92%